MENGULIK SEJARAH PERKEMBANGAN TAFSIR ISYARI DAN PANDANGAN PARA ULAMA - sholiha, Amaliatus; Putri, Ananda Rizki Prianka; Muttaqin, Muhammad Faiz Lubba Dzal (LPPM IAI Hasanuddin Pare-Kediri, 2024)
The science of the interpretation of the Qur'an continues to develop from time to time. These movements occur in various matters concerning the interpretation of the Qur'an such as methods, approaches, and also styles of interpretation. One form of interpretation that has developed is isyari interpretation. Isyari interpretation also causes problems between scholars with various views. This study aims to discuss and explore more about the history of the emergence of isyari interpretation and its development from time to time accompanied by the views of scholars at that time. The results of the analysis of this article are expected to have a positive influence, both in theory and practice. Theoretically, this research aims to provide an initial understanding and insight into the history of the emergence of isyari tafsir and its development from time to time accompanied by the views of the scholars at that time. While practically, this research is expected to be used as a basis in addressing the differences of opinion regarding the interpretation interpreted in isyari. The method used in this research is qualitative, using literature review. The main data sources used are books related to the discussion and the supporting sources are journals related to the discussion to help analyze the problem. The data processing technique used is by reading and understanding various literature related to the discussion, then analyzing the contents to get conclusions from several data sources used.